2012
DOI: 10.1007/s11738-012-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

Responses to excess iron in sweet potato: impacts on growth, enzyme activities, mineral concentrations, and anatomy

Abstract: Your article is protected by copyright and all rights are held exclusively by Franciszek Górski Institute of Plant Physiology, Polish Academy of Sciences, Kraków. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your work, please use the accepted author's version for posting to your own website or your institution's repository. You may further deposit the accepted author's version on a funder's repository at a funder's request, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…Esses autores observaram efeitos significativos do excesso de Fe sobre a relação parte aérea/raízes somente em concentrações de Fe acima de 1,43 mM e após 60 dias de tratamento. Em Excesso de ferro sobre o crescimento e a composição mineral em Eugenia uniflora L. * Médias seguidas pela mesma letra minúscula entre diferentes concentrações de FeEDTA para o mesmo DAT e pela mesma letra maiúscula entre diferentes DAT para a mesma concentração de FeEDTA não diferem estatisticamente pelo teste Duncan (p<0,05) Figura 3 -Massa seca de folhas, caules e raízes de plantas jovens de Eugenia uniflora, 15, 30 e 45 dias após tratamento (DAT) com diferentes concentrações de FeEDTA batata doce, entretanto, a relação massa seca parte aérea/ raízes aumentou em concentração de Fe de 0,9 mM, mas decresceu em concentração de 4,5 mM (ADAMSKI et al, 2012). Embora os mecanismos que governam a partição da biomassa em plantas ainda sejam bastante limitados (MARSCHNER; KIRKBY;CAKMAK, 1996), esse maior decréscimo na massa foliar em relação à massa radicular causado por Fe em excesso é sugestivo de estar ocorrendo uma interferência no aparato fotossintético destas plantas.…”
Section: Resultsunclassified
“…Esses autores observaram efeitos significativos do excesso de Fe sobre a relação parte aérea/raízes somente em concentrações de Fe acima de 1,43 mM e após 60 dias de tratamento. Em Excesso de ferro sobre o crescimento e a composição mineral em Eugenia uniflora L. * Médias seguidas pela mesma letra minúscula entre diferentes concentrações de FeEDTA para o mesmo DAT e pela mesma letra maiúscula entre diferentes DAT para a mesma concentração de FeEDTA não diferem estatisticamente pelo teste Duncan (p<0,05) Figura 3 -Massa seca de folhas, caules e raízes de plantas jovens de Eugenia uniflora, 15, 30 e 45 dias após tratamento (DAT) com diferentes concentrações de FeEDTA batata doce, entretanto, a relação massa seca parte aérea/ raízes aumentou em concentração de Fe de 0,9 mM, mas decresceu em concentração de 4,5 mM (ADAMSKI et al, 2012). Embora os mecanismos que governam a partição da biomassa em plantas ainda sejam bastante limitados (MARSCHNER; KIRKBY;CAKMAK, 1996), esse maior decréscimo na massa foliar em relação à massa radicular causado por Fe em excesso é sugestivo de estar ocorrendo uma interferência no aparato fotossintético destas plantas.…”
Section: Resultsunclassified
“…Other parameters were only slightly altered during the plant development. The provision of potato plants (variety ILS19) with 9.0 mM Fe and Hoagland growing medium contributed to an increase in F 0 , F m , and PI (Adamski et al 2012). At the same time, it was found that water scarcity and high light intensity [above 300 µmol(photon) m -2 s -1 ] caused an increase in F 0 and a decrease in F m in potato plants of the Kufri Sindhuri variety (Basu et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Iron is found to be localized inside the different cellular compartments such as chloroplasts, mitochondria, and vacuoles (Jeong and Guerinot 2009;Adamski et al 2012;Vigani et al 2013). It also acts as a redox cofactor in a variety of plant cellular metabolism (Puig et al 2005).…”
Section: Iron (Fe)mentioning
confidence: 99%
“…It also acts as a redox cofactor in a variety of plant cellular metabolism (Puig et al 2005). Iron (Fe) is an unavoidable and one of the most prominent constituent of a number of proteins and enzymes that plays important roles in key metabolic processes, including cellular respiration, oxygen transport, lipid metabolism, the tricarboxylic acid (TCA) cycle, gene regulation, synthesis of metabolic intermediates, and DNA biosynthesis as well as making it essential for photosynthesis and chlorophyll biosynthesis (Jeong and Connolly 2009;Adamski et al 2012). To organize the range of physiological and metabolic function in a convectional manner and to minimize nutritional disorder both the abundance and deficiency of micronutrients should be maintained properly.…”
Section: Iron (Fe)mentioning
confidence: 99%